Dynamics of Non-Hajj Visa Regulations: Literature Review of the Ministry of Hajj and Umrah of Saudi Arabia 2024 - Fany Arifin (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The use of non-Hajj visas during the Hajj pilgrimage has become a serious issue, impacting the legal aspects, security, and validity of the pilgrimage. This phenomenon has intensified due to the lengthy Hajj waiting list in Indonesia and the high public enthusiasm for performing the pilgrimage. The Saudi Arabian government has responded to this situation by tightening Hajj visa regulations, issuing a fatwa prohibiting Hajj without an official visa, and imposing strict sanctions in the form of fines, deportation, and a ban on entry to Saudi Arabia. This study aims to analyze the dynamics of non-Hajj visa regulations implemented by the Saudi Arabian Ministry of Hajj and Umrah in 2024 and their implications for the sustainability of Hajj and the protection of pilgrims. The research method used is a qualitative literature review approach, through the examination of journal articles, scientific books, legal documents, and official regulations related to Hajj implementation. The results show that the use of non-Hajj visas not only violates state law and sharia provisions but also has the potential to harm pilgrims and their countries of origin. Hajj visa regulations serve as a public policy instrument to maintain order, ensure fair quota distribution, and ensure the safety of pilgrims. This study recommends strengthening government oversight, increasing public literacy and education regarding Hajj visas, and improving the quality of human resources for pilgrims and Hajj guides to prevent future non-Hajj visa practices.